Automatic products design using multi¬puprose and dedicated software packages and systems - Gatalo, Ratko; Zeljković, Milan; Navalušić, Slobodan; Novaković, Dragoljub (Journal of Production Engineering, 1993)
In the paper, the original results of the development of the system for automatic product design are presented. It begins with the concept of the global system model for the automatic design of parts and products. This model forms the basis for the development of all subsystems comprising the SAPOR system. Then, it provides a state-of-the-art overview of particular subsystems designed for the automatic design of assemblies and parts. In both cases, proprietary solutions and solutions based on multi-purpose CAD systems upgrades are demonstrated. As an example of a multi-purpose CAD system upgrade, the use of AutoCAD, MEW, and IDEAS is showcased. It is emphasized that multi-purpose CAD systems upgrades are very suitable due to the potential for interaction between the user and the computer. This interaction is particularly important during the assembly design phase and product concept design phase.